PENDIDIKAN ISLAM MULTIKULTURALISME - Saihu Saihu (STIT AL-AMIN KREO TANGERANG, 2018)
A simple definition of education is how to improve the potential of human life adapted with our values and cultures. While multiculturalism many experts define a diverse or compound. Indonesia has got more than 300 tribes actually they have different cultures, values, languages etc that sometimes happening a conflict. in this way Islamic Multiculturalism Education expected can solve the problems in our state or communities, at least give some awareness that conflict is not good situation to developed. Education has to capable give the bids which a smart solution, such as designing material, method and curriculum that make the communities understood the importance of tolerance, honor each other, can live together with different background